High-strength anti-steam oxidation coating material and coating, preparation method and application thereof

By combining the solid and liquid phase components of the high-strength anti-steam oxidation coating material, a double-layer structure metallurgical combination coating is formed, which solves the problem of degradation of the mechanical properties of the coating in high-temperature environments and improves the inner wall of the flow component The antioxidant capacity and service life achieve low-cost and efficient coating preparation.

CN119307124AActive Publication Date: 2025-01-14HUANENG HUNAN YUEYANG POWER GENERATION CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411586246.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-14
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The mechanical properties of the existing coatings in high temperature environments lead to accelerated corrosion of the inner wall of the flow components, and the existing treatment methods are costly or difficult to meet the needs of industrial operation.

Method used

Using high-strength anti-steam oxidation coating material, the components include solid phase components (Cr, Ni, Co, Al, Ti, Si, Nb, La) and liquid phase components, the coating slurry is formed by mixing and ball milling, and the coating is coated. The coating is carried out and dried, cured and calcined at high temperature to form a two-layer structure metallurgical-bound coating.

Benefits of technology

It improves the thermal stability, thermal creep resistance and high-temperature durability of the coating, prevents cracking, and significantly improves the oxidation resistance and service life of the inner wall of the flowing component, which is simple to operate and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005124357290000101
    Figure BDA0005124357290000101
  • Figure HDA0005124357310000011
    Figure HDA0005124357310000011
  • Figure HDA0005124357310000012
    Figure HDA0005124357310000012
Patent Text Reader

Abstract

The invention discloses a high-strength anti-steam oxidation coating material and a coating, a preparation method and application thereof, and belongs to the technical field of corrosion prevention of inner walls of through-flow components of thermal power generating units. The high-strength steam oxidation-resistant coating material disclosed by the invention is composed of the solid-phase component and the liquid-phase component, and all the components play a synergistic role, so that the steam oxidation resistance of a coating is improved, and meanwhile, the mechanical property of the coating is enhanced, so that the coating is prevented from cracking in the service process, and the service life of the coating is prolonged. The problem that an existing coating cracks in a high-temperature environment is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anti-corrosion of inner walls of flow-through components of thermal power units, and in particular relates to a high-strength steam oxidation resistant coating material and a coating, a preparation method and an application thereof. Background Art

[0002] The circulation components of thermal power units usually operate under high temperature and high pressure conditions, especially under supercritical pressure. Steam and water have the same solubility characteristics. This high temperature and high pressure environment causes oxidation reaction on the inner wall of the metal pipe of the circulation components. At the same time, if the content of metal oxide corrosion products in the boiler feed water system of the unit and various acids, alkalis and salts in the boiler feed water is not strictly controlled, it will accelerate the oxidation process of the metal pipe. If no effective treatment measures are taken, a large amount of non-dense oxide corrosion products will be deposited on the inner wall of the high temperature and high pressure steam pipe. This non-dense oxide film structure is easy to accelerate the shedding, regrowth and re-shedding of the oxide film, further aggravating the oxidation process.

[0003] In response to the above phenomenon, technicians usually use a combined flushing and purging method with ammonia and oxygen. This method can cause high-temperature water vapor to react chemically with the metal on the inner wall of the pipe quickly to form a dense double-layer protective oxide film, which can be tightly bonded to the metal parent material without being loose, has good surface properties, and can prevent further corrosion of the metal. However, this method requires the addition of chemical substances such as ammonia and oxygen, and requires precise purging treatment, so the treatment cost is high and it is difficult to meet the needs of industrial operation. Some technicians also coat the inner wall of the group flow components with a composite coating of Cr-based components to improve the steam oxidation resistance of the group flow components. However, with the increase of service time, under high temperature conditions, the thermal stress of the coating material increases. At the same time, the difference in thermal expansion coefficients between the coating and the base material may also lead to stress concentration, resulting in a decrease in the mechanical properties of the Cr coating such as yield strength and tensile strength, which in turn causes cracks and accelerates the corrosion of the inner wall of the flow component. Summary of the invention

[0004] The purpose of the present invention is to provide a high-strength steam oxidation resistant coating material and its coating, preparation method and application, so as to solve the technical problem that the existing coating has mechanical property degradation and cracking in a high temperature environment.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention discloses a high-strength steam oxidation resistant coating material, wherein the high-strength steam oxidation resistant coating comprises a solid phase component and a liquid phase component;

[0007] In terms of mass percentage, the solid phase components include:

[0008] 44%-60% Cr, 5%-30% Ni, 2%-8% Co, 3%-5% Al, 2%-10% Ti, 2%-5% Si, 2%-10% Nb and 4.4%-5% La;

[0009] The liquid phase component is a metal oxide solution.

[0010] Furthermore, the dosage ratio of the solid phase component to the liquid phase component is 10g:1-5mL.

[0011] Furthermore, the metal oxide solution is obtained by mixing a metal oxide and a solvent; the metal oxide is CrO 3 、MgO、Si 3 N 4 and ZnO or both;

[0012] The mass fraction of the metal oxide solution is 10%-30%.

[0013] Furthermore, the solvent is Al(H 2 PO 4 ) and water glass.

[0014] The present invention also discloses a method for preparing a high-strength steam oxidation resistant coating, which is prepared using the above-mentioned high-strength steam oxidation resistant coating material, and comprises the following steps:

[0015] Weighing raw materials of solid phase components according to mass percentage and mixing them to obtain solid phase components;

[0016] Weighing raw materials of liquid phase components, stirring and mixing, and obtaining liquid phase components;

[0017] After mixing the solid phase component and the liquid phase component, a coating slurry is obtained;

[0018] The coating slurry is coated on the surface of the substrate, and then dried, cured and heat-treated in sequence to obtain a high-strength steam oxidation-resistant coating on the surface of the substrate.

[0019] Furthermore, the raw materials of the solid phase component are weighed according to the mass percentage, mixed for 12-24 hours, and then ball milled for 6-24 hours to obtain the solid phase component;

[0020] The solid phase component and the liquid phase component are mixed, stirred for 2-4 hours, and then ball milled for 6-24 hours to obtain a coating slurry.

[0021] Furthermore, the coating pressure is 0.5-2.0 MPa; the thickness of the coating slurry is 0.1-1.0 mm; the coverage of the coating slurry on the surface of the substrate is not less than 98%;

[0022] The air-drying method is natural air-drying, and the natural air-drying time is 24-48 hours; the curing temperature is 300-450°C, and the time is 24-48 hours; the heat treatment method is high-temperature calcination, and the high-temperature calcination is carried out under an inert atmosphere at a temperature of 980-1150°C and a time of 8-15 minutes.

[0023] Furthermore, the type of the substrate is TP304H, TP347H, Super304H, TP347HFG, HR3C or nickel-iron based alloy.

[0024] The invention also discloses a high-strength steam oxidation resistant coating prepared by the preparation method.

[0025] The invention also discloses the application of the high-strength steam oxidation resistant coating in the corrosion protection of the inner wall of the flow-through components of a thermal power unit.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The invention discloses a high-strength steam oxidation resistant coating material, which consists of a solid phase component and a liquid phase component. The components work synergistically to improve the steam oxidation resistance of the Cr / Ni-Cr-based coating and strengthen its mechanical properties to prevent cracking during service. Ni works synergistically with other elements to form a stable solid solution structure, improve the thermal stability and thermal creep resistance of the coating, and improve the strength and plasticity. Co has an important influence on the formed solid solution structure, improves the grain boundary strengthening effect in the coating, and improves its high-temperature durability. Cr forms a dense oxide film at high temperature, which can effectively prevent oxygen corrosion and oxidation reaction of the alloy matrix, thereby improving the service life. Al and Ti are main elements of γ' phase in high-temperature alloys. Increasing the Al and Ti contents will increase the volume fraction of the γ' phase, increase its dissolution temperature, and change its morphology from spherical to cubic, thereby significantly improving the high-temperature strength and solving the problem of cracking of the existing coating in a high-temperature environment.

[0028] Furthermore, Al can also promote Al 2 O 3 The Ti element is one of the main elements forming MC carbides, which helps to stabilize the formation of TiC and improve the alloy's resistance to hot corrosion.

[0029] Furthermore, La can react with non-metallic impurities in the coating to form compounds, part of which is eliminated and part of which is retained in the alloy to play a role of heterogeneous nucleation, eliminating or reducing the harm of impurities and improving the quality and purity of the coating.

[0030] The present invention also discloses a coating preparation method based on the above-mentioned high-strength steam oxidation resistant coating material. The method adopts simple coating to realize the coating preparation, is simple to operate, and has low cost. It can be applied to the preparation of inner wall coatings of flow-through components with large aspect ratio, and has broad application prospects.

[0031] Furthermore, by adjusting the thickness of the coating slurry, the coating thickness on the substrate surface can be adjusted, and the required thickness coating can be flexibly prepared according to the service conditions and environment; according to relevant experimental results, applying a coating slurry of 0.1-1.0mm can form a 45-62μm coating on the substrate surface.

[0032] Furthermore, a double-layer structure and a metallurgical bonding coating are formed on the surface of the substrate by heat treatment, which significantly improves the bonding force between the coating and the substrate and improves the oxidation resistance of the substrate in a pure water vapor environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 A schematic cross-sectional view of a high-strength steam oxidation resistant coating prepared in the present invention;

[0034] Figure 2 The critical cracking strength data of the high-strength steam oxidation resistant coating prepared by the present invention. DETAILED DESCRIPTION

[0035] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0036] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0037] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0038] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0039] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0040] The first aspect of the present invention provides a high-strength steam oxidation resistant coating material, which is composed of a solid phase component and a liquid phase component; wherein, in terms of mass percentage, the solid phase component includes:

[0041] 45%-70% Cr, 5%-30% Ni, 2%-8% Co, 3%-5% Al, 2%-10% Ti, 2%-5% Si, 2%-10% Nb and 4.4%-5% La;

[0042] The liquid phase component is a metal oxide solution; the above components improve the steam oxidation resistance of the Cr / Ni-Cr-based coating and strengthen its mechanical properties to prevent it from cracking during service.

[0043] Preferably, the dosage ratio of the solid phase component to the liquid phase component is 10 g: 1-5 mL.

[0044] Preferably, the metal oxide solution is obtained by mixing a metal oxide and a solvent; the metal oxide is CrO 3 、MgO、Si 3 N 4 and ZnO, the mass fraction of the formed metal oxide solution is 10-30%.

[0045] Preferably, the solvent is Al(H 2 PO 4 ), one or more of water glass and organic binder.

[0046] The second aspect of the present invention provides a method for preparing a coating using the above-mentioned high-strength steam oxidation resistant coating material, comprising the following steps:

[0047] According to mass percentage, 44%-60% Cr, 5%-30% Ni, 2%-8% Co, 3%-5% Al, 2%-10% Ti, 2%-5% Si, 2%-10% Nb and 4.4%-5% La are weighed, mixed for 12-24 hours, and then ball-milled for 6-24 hours to obtain a solid phase component;

[0048] Weighing raw materials of liquid phase components, stirring and mixing, and obtaining liquid phase components;

[0049] The solid phase component and the liquid phase component are mixed, stirred for 2-4 hours, and then ball milled for 6-24 hours to obtain a coating slurry;

[0050] The coating slurry is coated on the surface of the substrate by artificial coating or spin coating, and then dried, cured and heat treated in sequence to obtain a high-strength steam oxidation resistant coating on the surface of the substrate.

[0051] Preferably, the coating pressure is 0.5-2.0MPa; the thickness of the coating slurry is 0.1-1.0mm; the coverage of the coating slurry on the substrate surface is not less than 98%; the air-drying method is natural air-drying, and the natural air-drying time is 24-48h; the curing temperature is 300-450℃, and the time is 24-48h.

[0052] Preferably, the substrate is made of austenitic steel, such as TP304H, TP347H, Super304H, TP347HFG, HR3C, nickel-iron based alloy, etc.

[0053] Preferably, the heat treatment is carried out by high-temperature sintering; the temperature of the high-temperature sintering is 980-1150° C., the time is 8-15 min, and it is carried out under the protection of an inert gas.

[0054] The third aspect of the present invention provides a high-strength steam oxidation resistant coating prepared by the above method, the coating structure is a double-layer structure, metallurgical bonding, and the thickness is 45-62 μm.

[0055] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0056] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0057] Example 1

[0058] A method for preparing a high-strength steam oxidation resistant coating comprises the following steps:

[0059] Step 1: 45% Cr, 30% Ni, 2% Co, 3% Al, 2% Ti, 5% Si, 8% Nb and 5% La were weighed in mass percentage, mixed for 12 hours, and then ball-milled for 12 hours to obtain a solid phase component;

[0060] Step 2: Al(H 2 PO 4 ), CrO 3 After mixing with MgO, a liquid phase component is obtained, wherein the mass fraction of the liquid phase component is 30%;

[0061] Step 3: The solid phase component and the liquid phase component were mixed at a solid-liquid ratio of 10 g: 5 mL, stirred for 4 h, and then ball-milled for 12 h to obtain a coating slurry;

[0062] Step 4: Apply the coating slurry to the surface of the TP304H substrate by manual brushing at a coating pressure of 0.5 MPa, with a coating thickness of 1.0 mm and a coverage rate of not less than 98%;

[0063] Step 5: After natural air drying for 48 hours, the substrate is cured at 300°C for 30 hours, and then calcined at 980°C for 8 minutes under the protection of an inert atmosphere to obtain a high-strength steam oxidation resistant coating on the substrate surface.

[0064] Example 2

[0065] A method for preparing a high-strength steam oxidation resistant coating comprises the following steps:

[0066] Step 1: 50% Cr, 15.6% Ni, 8% Co, 5% Al, 10% Ti, 5% Si, 2% Nb and 4.4% La were weighed in mass percentage, mixed for 24 hours, and then ball-milled for 24 hours to obtain a solid phase component;

[0067] Step 2: Mix water glass and Si 3 N 4 After mixing, a liquid phase component is obtained, wherein the mass fraction of the liquid phase component is 10%;

[0068] Step 3: The solid phase component and the liquid phase component were mixed at a solid-liquid ratio of 10 g: 1 mL, stirred for 2 h, and then ball-milled for 24 h to obtain a coating slurry;

[0069] Step 4: Apply the coating slurry to the surface of the Super304H substrate by manual brushing at a coating pressure of 2.0 MPa, with a thickness of 0.1 mm and a coverage rate of not less than 98%;

[0070] Step 5: After natural air drying for 24 hours, the substrate is cured at 450°C for 24 hours, and then calcined at 1040°C for 10 minutes under the protection of an inert atmosphere to obtain a high-strength steam oxidation resistant coating on the substrate surface.

[0071] Example 3

[0072] A method for preparing a high-strength steam oxidation resistant coating comprises the following steps:

[0073] Step 1: 60% Cr, 5% Ni, 8% Co, 5% Al, 2.6% Ti, 5% Si, 10% Nb and 4.4% La were weighed in mass percentage, mixed for 24 hours, and then ball-milled for 24 hours to obtain a solid phase component;

[0074] Step 2: Al(H 2 PO 4 )、Water glass、MgO、Si 3 N 4 After mixing with ZnO, a liquid phase component is obtained, wherein the mass fraction of the liquid phase component is 25%;

[0075] Step 3: The solid phase component and the liquid phase component were mixed at a solid-liquid ratio of 10 g: 5 mL, stirred for 2 h, and then ball-milled for 20 h to obtain a coating slurry;

[0076] Step 4: Apply the coating slurry to the surface of the TP347HFG substrate by manual brushing at a coating pressure of 2.0 MPa, with a thickness of 0.5 mm and a coverage rate of not less than 98%;

[0077] Step 5: After natural air drying for 24 hours, the substrate is cured at 450°C for 24 hours, and then calcined at 1150°C for 12 minutes under the protection of an inert atmosphere to obtain a high-strength steam oxidation resistant coating on the substrate surface.

[0078] Example 4

[0079] A method for preparing a high-strength steam oxidation resistant coating comprises the following steps:

[0080] Step 1: 60% Cr, 5% Ni, 8% Co, 5% Al, 2.6% Ti, 5% Si, 10% Nb and 4.4% La were weighed in mass percentage, mixed for 24 hours, and then ball-milled for 24 hours to obtain a solid phase component;

[0081] Step 2: Al(H 2 PO 4 )、Water glass、MgO、Si 3 N 4 After mixing with ZnO, a liquid phase component is obtained, wherein the mass fraction of the liquid phase component is 25%;

[0082] Step 3: The solid phase component and the liquid phase component were mixed at a solid-liquid ratio of 10 g: 5 mL, stirred for 2 h, and then ball-milled for 20 h to obtain a coating slurry;

[0083] Step 4: Apply the coating slurry to the surface of the TP347HFG substrate by manual brushing at a coating pressure of 2.0 MPa, with a thickness of 0.8 mm and a coverage rate of not less than 98%;

[0084] Step 5: After natural air drying for 24 hours, the substrate is cured at 450°C for 24 hours, and then calcined at 1000°C for 10 minutes under the protection of an inert atmosphere to obtain a high-strength steam oxidation resistant coating on the substrate surface.

[0085] Example 5

[0086] A method for preparing a high-strength steam oxidation resistant coating comprises the following steps:

[0087] Step 1: 52% Cr, 13% Ni, 8% Co, 5% Al, 2.6% Ti, 5% Si, 10% Nb and 4.4% La were weighed in mass percentage, mixed for 24 hours, and then ball-milled for 24 hours to obtain a solid phase component;

[0088] Step 2: Al(H 2 PO 4 ), water glass, MgO, Si 3 N 4 After mixing with ZnO, a liquid phase component is obtained, wherein the mass fraction of the liquid phase component is 30%;

[0089] Step 3: The solid phase component and the liquid phase component were mixed at a solid-liquid ratio of 10 g: 5 mL, stirred for 2 h, and then ball-milled for 20 h to obtain a coating slurry;

[0090] Step 4: Apply the coating slurry to the surface of the TP347HFG substrate by manual brushing at a coating pressure of 2.0 MPa, with a thickness of 0.8 mm and a coverage rate of not less than 98%;

[0091] Step 5: After natural air drying for 24 hours, the substrate is cured at 450°C for 24 hours, and then calcined at 1150°C for 15 minutes under the protection of an inert atmosphere to obtain a high-strength steam oxidation resistant coating on the substrate surface.

[0092] Example 6

[0093] A method for preparing a high-strength steam oxidation resistant coating comprises the following steps:

[0094] Step 1: 60% Cr, 5% Ni, 8% Co, 5% Al, 2.6% Ti, 5% Si, 10% Nb and 4.4% La were weighed in mass percentage, mixed for 24 hours, and then ball-milled for 24 hours to obtain a solid phase component;

[0095] Step 2: Al(H 2 PO 4 ), water glass, MgO, Si 3 N 4 After mixing with ZnO, a liquid phase component is obtained, wherein the mass fraction of the liquid phase component is 25%;

[0096] Step 3: The solid phase component and the liquid phase component were mixed at a solid-liquid ratio of 10 g: 5 mL, stirred for 2 h, and then ball-milled for 20 h to obtain a coating slurry;

[0097] Step 4: Apply the coating slurry to the surface of the TP347HFG substrate by manual brushing at a coating pressure of 0.8 MPa, with a coating thickness of 1.0 mm and a coverage rate of not less than 98%;

[0098] Step 5: After natural air drying for 40 hours, the substrate is cured at 450°C for 24 hours, and then calcined at 1000°C for 10 minutes under the protection of an inert atmosphere to obtain a high-strength steam oxidation resistant coating on the substrate surface.

[0099] Example 7

[0100] A method for preparing a high-strength steam oxidation resistant coating comprises the following steps:

[0101] Step 1: 60% Cr, 5% Ni, 8% Co, 5% Al, 2.6% Ti, 5% Si, 10% Nb and 4.4% La were weighed in mass percentage, mixed for 24 hours, and then ball-milled for 24 hours to obtain a solid phase component;

[0102] Step 2: Al(H 2 PO 4 ), water glass, MgO, Si 3 N 4 After mixing with ZnO, a liquid phase component is obtained, wherein the mass fraction of the liquid phase component is 25%;

[0103] Step 3: The solid phase component and the liquid phase component were mixed at a solid-liquid ratio of 10 g: 5 mL, stirred for 2 h, and then ball-milled for 20 h to obtain a coating slurry;

[0104] Step 4: Apply the coating slurry to the surface of the TP347HFG substrate by manual brushing at a coating pressure of 2.0 MPa, with a thickness of 0.5 mm and a coverage rate of not less than 98%;

[0105] Step 5: After natural air drying for 24 hours, the substrate is cured at 450°C for 24 hours, and then calcined at 995°C for 12 minutes under the protection of an inert atmosphere to obtain a high-strength steam oxidation resistant coating on the substrate surface.

[0106] Figure 1 This is a cross-sectional schematic diagram of the high-strength steam-oxidation resistant coating prepared in the present invention. It can be seen from the figure that the high-strength steam-oxidation resistant coating is a double-layer structure and is metallurgically bonded to the substrate. When the coating thickness is in the range of 0.1-1.0 mm, the coating thickness is 45-62 μm.

[0107] Figure 2 The data shown are the critical cracking strength data of the high-strength steam oxidation resistant coating prepared by the present invention. The coating prepared by the material of the present invention has high strength at room temperature and high temperature of 650° C., and can effectively reduce the occurrence of cracking.

[0108] Table 1 shows the steam oxidation resistance data of the high-strength steam oxidation resistant coatings obtained in different embodiments. It can be seen from the table that, compared with the base alloy, the steam oxidation resistance of the coating is increased several times, which significantly improves the steam oxidation resistance.

[0109] Table 1 shows the steam oxidation resistance data of high-strength steam oxidation resistant coatings obtained in different embodiments.

[0110]

[0111] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A high-strength steam oxidation resistant coating material, characterized in that: The composition of the high-strength steam oxidation resistant coating includes a solid phase component and a liquid phase component; In terms of mass percentage, the solid phase components include: 44%-60% Cr, 5%-30% Ni, 2%-8% Co, 3%-5% Al, 2%-10% Ti, 2%-5% Si, 2%-10% Nb and 4.4%-5% La; The liquid phase component is a metal oxide solution.

2. The high-strength steam oxidation resistant coating material according to claim 1, characterized in that: The dosage ratio of the solid phase component to the liquid phase component is 10g:1-5mL.

3. The high-strength steam oxidation resistant coating material according to claim 1, characterized in that: The metal oxide solution is obtained by mixing a metal oxide and a solvent; the metal oxide is one or two of CrO3, MgO, Si3N4 and ZnO; The mass fraction of the metal oxide solution is 10%-30%.

4. The high-strength steam oxidation resistant coating material according to claim 1, characterized in that: The solvent is one or more of Al(H2PO4) and water glass.

5. A method for preparing a high-strength steam oxidation resistant coating, characterized in that: The high-strength steam oxidation resistant coating material according to any one of claims 1 to 4 is prepared, comprising the following steps: Weighing raw materials of solid phase components according to mass percentage and mixing them to obtain solid phase components; Weighing raw materials of liquid phase components, stirring and mixing, and obtaining liquid phase components; After mixing the solid phase component and the liquid phase component, a coating slurry is obtained; The coating slurry is coated on the surface of the substrate, and then dried, cured and heat-treated in sequence to obtain a high-strength steam oxidation-resistant coating on the surface of the substrate.

6. The method for preparing a high-strength steam oxidation resistant coating according to claim 5, characterized in that: The raw materials of the solid phase component are weighed according to the mass percentage, mixed for 12-24 hours, and then ball-milled for 6-24 hours to obtain the solid phase component; The solid phase component and the liquid phase component are mixed, stirred for 2-4 hours, and then ball milled for 6-24 hours to obtain a coating slurry.

7. The method for preparing a high-strength steam oxidation resistant coating according to claim 5, characterized in that: The coating pressure is 0.5-2.0MPa; the thickness of the coating slurry is 0.1-1.0mm; the coverage of the coating slurry on the surface of the substrate is not less than 98%; The air-drying method is natural air-drying, and the natural air-drying time is 24-48 hours; the curing temperature is 300-450°C, and the time is 24-48 hours; the heat treatment method is high-temperature calcination, and the high-temperature calcination is carried out under an inert atmosphere at a temperature of 980-1150°C and a time of 8-15 minutes.

8. The method for preparing a high-strength steam oxidation resistant coating according to claim 5, characterized in that: The type of the substrate is TP304H, TP347H, Super304H, TP347HFG, HR3C or nickel-iron based alloy.

9. A high-strength steam oxidation resistant coating, characterized in that: The preparation method is described in any one of claims 5 to 8.

10. Use of the high-strength steam oxidation resistant coating according to claim 9 in the corrosion protection of the inner wall of flow-through components of thermal power units.

Citation Information

Patent Citations

  • Preparation method of obdurability high-temperature steam oxidation resistant coating

    CN113802088A

  • Coating system for high temperature stainless steel

    CN1433486A

  • Method and apparatus for improving steam oxidation resistance of small-diameter boiler tube of coal-fired boiler

    EP4403669A1

  • Coating membrane with steam oxidation resistive property and gasturbine blade coated with the same membrane

    JP2002012933A